Evaluation of health service providers by consumers through the Analytic Hierarchy Process Method - Wollmann, Dewey; Steiner, Maria Teresinha Arns; Vieira, Guilherme Ernani; Steiner, Patrícia Arns (Revista de Saúde Pública, 2012)
OBJECTIVE: To assess the quality of services offered by health service providers, according to the perception of consumers. METHODS: A cross-sectional study with 360 consumers from seven health service providers in the metropolitan area of Curitiba, PR, in 2008, was performed. An individual questionnaire measuring the consumers' preferences in relation to six attributes (location of service points; effectiveness of doctors, clinics and hospitals; promptness and kindness when caring for patients and family members; ease of access to the authorization forms for consultations; price; diversity of available doctors, clinics and hospitals) for each one of the analyzed health service providers was carried out. The Analytic Hierarchy Process (AHP), a multiple criteria tool for decision analysis and planning, was used to analyze the responses. RESULTS: The attribute most valued by the consumers was "price". The companies were grouped into two sets, regarding the mentioned attributes: two had lower preference (between 19% and 23%) and five, higher preference (around 10% each). CONCLUSIONS: With this type of research, health service providers could reshape their structures, processes, prices and accredited networks, in order to improve their market strategy.